Routledge Handbook of Seabed Mining and the Law of the Sea (Taylor & Francis, 2024)
Deep-sea mining; Dispute settlement; Law of the Sea; State regulation
English
Keywords: International maritime law; Jurisprudence & general issues; Deep-sea mining; Dispute settlement; Law of the Sea; State regulation